Politics of Legitimation - Hasanah, Mahesti (PCD Journal, 2022)
This research discusses contract farming—an agreement between farmers and processing and/or marketing firms, usually agribusiness transnational companies (TNCs), under a specific arrangement that commonly includes predetermined prices for the production and supply of agricultural products—in a transnational policy context. The study is dominated by institutionalism and materialism approaches which hold that structural changes coincide with economic development. However, this approaches raises a question about the role of actors in instituting, transferring, and challenging the norms of contract farming. This research seeks to challenge the literature by focusing on how contract farming, as a dual process, constitutes a territory for its actors to claim and reclaim their authority. Drawing on the implementation of agreements between TNCs and small farmers in Davao, Mindanao, we discuss the legitimation process within a context of strong state political control and complicated global market flows. Specifically, this research aims to understand how contract farming institutes a particular type of legitimation through the influence of transnational policy. Using the organisational and institutional legitimation approaches, we understand contract farming as a fluid and openly contested distributing authority. This research uses four data collection methods: desk studies, interviews, focus group discussions, and observation.